Assessment of Occupants’ Satisfaction with Noise in Kilang Kelapa Sawit Bukit Pasir Sdn. Bhd. - Siti Nur Asyiqin Ahmad Sahlan; Abdul Zaki Abdul Wahid; Muhammad Faiz Haikal Ali (Progress in Engineering Application and Technology, 2024)
The issue of excessive noise and its effects on employee performance and health. This research is focused on Kilang Kelapa Sawit Bukit Pasir Sdn Bhd, where the aim is to improve the quality and safety of the workers. For reference, the researcher uses the Occupational Health and Safety Act 1994 (OSHA 1994), which requires employers to provide PPE to employees to prevent harm from excessive noise. This study aims to assess the excessive noise and impact on workers in the factory that have been stated before. For the measurement of noise level. The researcher used a dosimeter and the noise risk assessment, the researcher chose personal monitoring as the method to identify.